Transition Program for Young Children with Special Needs: Parents’ Experiences - Nur Azizah; Rafika Rahmawati; Edi Purwanta (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The successful transition process in early childhood led to future school outcomes. The aim of the research was to explore the experiences of parents of children with special needs in transitioning their children to school. The study used a qualitative approach involving 17 parents of young children with special needs receiving education in special schools in Yogyakarta. Focus group discussion was used to collect the data. Data collected from Focus Group Discussion was analysed using thematic analysis. Findings from the study show that parents of children with mild special needs do not have specific preparation in transitioning their children to school, school provided a week at the beginning of the school period for parents to stay and assist their children in the classes. Parents believe that there is no adequate support for transitioning their children to school and that condition exaggerates their anxieties when leaving their children at school. A structured transition program is needed as the implication of this study.